Experimental Study of Pulsed Electrical Discharge in Cylindrically-Tipped of Plasma Switch - Ahmed, Ala’ F.; Hasaani, A. S. Hasaani (Iraqi Journal of Science, 2022)
In this research pulse high voltage circuit was used including resistance,inductance and capacitor to achieve an experiment of cylindrically-tipped of plasmaswitch .The charging voltage of up to 9kV using Rogowski coil and current-shuntresistance (CVR) used to measure pulsed electrical discharge (PED). The current inboth self-triggering and third-electrode triggering modes. The pulsed current peaks4kA and the duration of circuit pulses were recorded between 0.1μs and 0.3μs. Theexperimental results has shown clearly the inductance effect in the circuit parts inunder damped oscillation regarding the value of circuit parts in addition to thedistance of the spark gap cylindrically-tipped electrodes during the plasmapropagates under air pressure with their circuit impedance. Under the range ofexperimental states (2-30)Ω nominal impedance ranges were recorded, rely on thegap and circuit parameters.